Biology and Control of Goosegrass in Sugarcane - Dennis Calvin Odero; Ron Rice; Les Baucum (EDIS, 2013)
Goosegrass is an annual plant that produces a prostrate, mat-like rosette with flattened stems radiating from a central point. It is often described as looking like someone has stepped in the middle of the plant, flattening it out. Because of the whitish to translucent color of the leaf sheath margins, goosegrass usually appears white to silver; this is why it is known as white or silver crabgrass. Goosegrass is found year-round in southern Florida and is commonly associated with newly planted and stubble (ratoon) sugarcane fields. This 3-page fact sheet was written by Dennis Calvin Odero, Ron Rice, and Les Baucum, and published by the UF Department of Agronomy, January 2013.